AUTHENTICITY IN BUILDING ADJUSTMENT SIMULATION (Case Study: Emergency Room of St. Elizabeth Hospital Semarang, Indonesia) - Sri Hartuti Wahyuningrum; Mustika Kusumaning Wardhani; Robert Rianto Widjaja (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
This paper aims to simulate adjustments for new functions in hospitals that respect the authenticity of cultural heritage buildings. The development of heritage buildings should be integrated, especially in adjusting building functions, such as room arrangement. The emergency room is a vital function for hospital services, and consideration is needed to arrange procedures. The research method chosen in this research is descriptive qualitative with a case study in the Magdalena Daeman building St Elizabeth Hospital. Design simulation can be realized by adjusting the standard emergency room requirements into the layout of the building. Additionally, cultural heritage buildings should be maintained to be used in operational functions by carrying out development. This study's results can be a guideline in developing new functions of cultural heritage buildings that meet the conservation technique guidelines.